The Influence of Time Management and Social Media Addiction on Academic Procrastination in Undergraduate Students - Mukarromah, Lutfi Ayu; Hakim, Gamma Rahmita Ureka (Universitas Negeri Malang, 2023)
This study aims to determine the effect of time management and social media addiction on academic procrastination in undergraduate students. The research method used is quantitative, with the incidental sampling technique. Respondents in this study amounted to 417 undergraduate students from universities in Malang City. The data was obtained from a questionnaire consisting of a time management scale, a social media addiction scale, and an academic procrastination scale. Test the hypothesis in this study using a multiple linear regression test with a coefficient of determination (R-squared) value of 0.481. The results showed a significant effect between time management, social media addiction and academic procrastination. Students with poor time management and social media addiction tend to have academic procrastination problems. Further research is needed to find out the factors that influence time management, social media addiction and academic procrastination in undergraduate students in more depth.